Fingernail Carriage of Methicillin-Resistant Staphylococcus aureus and Possible Correlation with Soft Tissue Infections in Children - Muschick, Kathryn D; LaCroix, Robin; McAdams, Jillian (Southern medical journal (Birmingham, Ala.), 2016)
Community-associated methicillin-resistant Staphylococcus aureus (MRSA) is a growing problem in the pediatric population, causing many soft tissue infections. This study was designed to examine fingernail carriage of MRSA in children and their caregivers as a possible link to community-associated MRSA soft tissue infections in children. We documented the prevalence of MRSA under the fingernails of children and the caregivers of pediatric patients with soft tissue infections and compared the prevalence with MRSA under the fingernails of children and the caregivers of children with no history of soft tissue infections. Children with soft tissue infections and their caregivers (50 subjects) had three fingernails of each hand swabbed and plated and these were compared with a control group of children and their caregivers (150 subjects) who had no history of MRSA or soft tissue infection. Caregivers and children in the study group were more likely than caregivers and the children in the control group to have MRSA under their fingernails (P < 0.05). Soft tissue infections in the study group were found most commonly in the diapering area (66%). MRSA carriage was evident under the fingernails of children and caregivers. Caregivers and their children who have soft tissue infections are more likely to have MRSA growth under fingernails than caregivers or their children who have no history of MRSA or soft tissue infections. Our study suggests that caregivers could be contributing to soft tissue infections in their children.